Informasi Elektronik Sebagai Alat Bukti dalam Perkara Perdata di Pengadilan - Agnes Sesilia Manasa; Wenly R. J. Lolong; Hendrasari B. R. Rawung (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Evidence plays an important role in evidence in the settlement of cases in court proceedings in civil cases. In civil law and litigation, evidence is very important because civil procedural law seeks formal truth only based on the evidence submitted by the parties in litigation in court. With technological advances, it also affects the applicable legal order, one of which is the addition of evidence, namely electronic evidence such as electronic information and electronic documents. The Civil Code even in its acar law book does not clearly regulate this electronic evidence, the regulation of electronic evidence is clearly regulated in the Electronic Information and Transaction Law (ITE). So that there are still many questions about the position and strength of electronic evidence in the settlement of cases in court such as civil cases.